Assistência estudantil e qualidade de vida relacionada à saúde bucal: um estudo de coorte - Souza, Fernanda Lavarda Ramos de (2025)
The process of democratizing public educational institutions and Brazilian society itself is aimed at reducing socio-economic inequalities. In addition to access to free public education, actions are needed to guarantee the permanence of students. The Brazilian National Student Assistance Policy aims to promote access, permanence and success considering social inclusion and the democratization of education through a set of actions, including assistance with student housing, food, financial aid and health care at federal universities and institutes. The Federal Institutes of Education, Science and Technology offer medium-level technical professional education courses all over the country, aiming to reach locations far from major urban centers and have a large number of teenagers enrolled on their campuses. In addition to being in a period of significant biological and psychosocial transformation and the development of new behaviors in relation to oral health, adolescents find themselves in a new setting, often far from their families. Knowing the perception and behavior of individuals in relation to their oral condition and the influence of oral health on their daily activities provides opportunities for planned services and programs. Therefore, the general objective of this study was to verify whether the use of student assistance services offered through the actions of the National Student Assistance Policy influences the oral health-related quality of life (OHRQoL) of students integrated secondary education at a Federal Institute in southern Brazil. All students starting the first year of high school integrated into technical education at four campuses were invited to take part. A prospective cohort was carried out, with data collection in the years 2023 and 2024. The main predictors were the use of dental services and the number of student assistance services used on the campus. The outcome considered were the Oral Impacts on Daily Performances (OIDP) scores (discrete variable) to assess the impacts affecting daily performance. Multilevel linear regression models were carried out to test the association between the outcome and the main predictors, estimating the regression coefficient, their respective standard error and p-values. A total of 199 adolescents took part in the study, which had a cohort retention rate of 84%. Students who did not use dental care services had lower OIDP scores over time (β=-0.53; p=0.01). However, when the adjustment variable reason for visiting the dentist was included, the statistically significant association was lost (β=-0.17; p=0.59). The greater the number of student assistance services used, the lower the average OIDP score (β=-0.98; p=0.03). As the number of services used by students increased, their OIDP scores decreased by an average of 0.1. The results confirm the initial hypothesis that the greater the number of services used, the greater the contribution to the student's OHRQoL. The findings corroborate the significant role of student assistance policies and contribute to highlighting the importance of implementing them from a comprehensive perspective, which provides a welcoming school trajectory and opportunities.